2016
DOI: 10.4103/0019-557x.177349
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health system delays among adult smear-positive tuberculosis patients diagnosed at medical colleges of Puducherry in south India

Abstract: Early diagnosis and prompt initiation of treatment are essential for an effective tuberculosis (TB) control program. This study was done to assess the extent of various delays among TB patients diagnosed at medical colleges of Puducherry. A cross-sectional study involving retrospective medical record review and prospective patient interviews was conducted in and around the union territory of Puducherry during the period 2009-10. Various delays and adjusted odds ratios (ORs) were calculated. Level of significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…As seen in most other studies, the present study also elicited that patient delay was the main contributor to the total diagnostic delay,[ 13 14 15 16 17 18 19 20 21 22 ] although few studies[ 23 24 ] found health system delay as the main contributor. In our setting, the ratio of patient delay and health system delay was 5:1; the corresponding figures were 3:1 in Sikkim;[ 13 ] 2.8:1 in Nepal;[ 14 ] 4.3:1 in Angola;[ 15 ]; 1.5:1 in Navi Mumbai;[ 16 ] 1.1:1 in Mandi;[ 17 ] 1.7:1 in Oromia;[ 18 ] 3.1:1 in Puducherry;[ 19 ]; 1.4:1 in Brazil;[ 21 ] and 2.5:1 in Argentina. [ 22 ]; 0.5:1 in Mumbai;[ 23 ]; and 0.6:1 in Indian literature;[ 24 ]…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As seen in most other studies, the present study also elicited that patient delay was the main contributor to the total diagnostic delay,[ 13 14 15 16 17 18 19 20 21 22 ] although few studies[ 23 24 ] found health system delay as the main contributor. In our setting, the ratio of patient delay and health system delay was 5:1; the corresponding figures were 3:1 in Sikkim;[ 13 ] 2.8:1 in Nepal;[ 14 ] 4.3:1 in Angola;[ 15 ]; 1.5:1 in Navi Mumbai;[ 16 ] 1.1:1 in Mandi;[ 17 ] 1.7:1 in Oromia;[ 18 ] 3.1:1 in Puducherry;[ 19 ]; 1.4:1 in Brazil;[ 21 ] and 2.5:1 in Argentina. [ 22 ]; 0.5:1 in Mumbai;[ 23 ]; and 0.6:1 in Indian literature;[ 24 ]…”
Section: Discussionsupporting
confidence: 84%
“…Patient delay represented 83.3% of total delay in our study; 75% in Sikkim;[ 13 ] 73% in Nepal;[ 14 ] 81% in Angola;[ 15 ] 59.5% in Navi Mumbai;[ 16 ] 53.6% in Mandi;[ 17 ] 64.4% in Oromia;[ 18 ] 75% in Puducherry;[ 19 ] 59% in Brazil;[ 21 ] 71.3% in Argentina. [ 22 ] and32.6% in Mumbai;[ 23 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though this region is not considered as having a high rate of incidence for TB, we found that the median of HSD in this region of Iran is higher than national value (52 vs. 42 days) [ 1 ]. Based on previous studies, there is a wide range of median HSD values, from 2 to 120 days, in industrialized and developing countries [ 15 , 17 , 23 , 61 – 63 ]. In this study, the median HSD was almost similar to studies in Malaysia (49 days), Vietnam (53 days), and New Zealand (49 days) [ 49 , 62 , 64 ]; lower than Mozambique (62 days), Pakistan (87 days), and Columbia (> 60 days) [ 1 , 39 , 52 , 65 ]; and higher than Taiwan (29 days), India (28 days), Nigeria (7 days), and Angola (7 days) [ 63 , 66 68 ].…”
Section: Discussionmentioning
confidence: 99%